‘Slip Out the Back Jack’: Why Applicants Ghost Potential Employers - Karl , Katherine A.; Peluchette , Joy V.; Neely, Andrea R. (American Journal of Management, 2021)
This study examined predictors of ‘ghosting’, an extreme form of applicant withdrawal in which applicants fail to appear for scheduled interviews and completely cease all communication. These predictors included frequency of recruiter communication, knowledge of the company, gender, conscientiousness, and helicopter parenting. All predictors were found to significantly predict ghosting such that frequency of recruiter communication and candidates’ knowledge about the firm influenced the level of attraction that candidates feel toward an organization which, in turn, influenced their likelihood to ghost an organization. Conscientiousness, gender and helicopter parenting also related to ghosting. Practical implications and future research directions are discussed.